Production without Empowerment: Work reorganization from the perspective of motor vehicle workers - Lewchuk, Wayne; Robertson, David (Capital & Class, 1997)
This paper examines the relationship between new forms of work organization and worker empowerment from the perspective of workers. The data is drawn from a survey of 5,635 Canadian automobile workers. Workers were asked questions about their work-load, health and safety conditions, empowerment, and relations with management. It examines what it is like to work in plants organized according to the principles of lean production and compares empowerment in lean plants and traditionally organized plants.

Working Conditions under Lean Production: A Worker-based Benchmarking Study - Lewchuk, Wayne; Robertson, David (Asia Pacific Business Review, 1996)
Benchmarking is being used extensively in management's drive to achieve ‘world class’ levels of performance. The majority of benchmarking studies have little if anything to say about working conditions or the tradeoffs between productivity improvements and the conditions of working life. This article is based on a study which focuses on working conditions as described by workers, raising questions about the tradeoffs betwcen work reorganization and the quality of working life under Lean Production. The results, based on a survey of 1670 workers at 16 different companies, suggest that work life under Lean Production has not improved. Compared with workers in traditional Fordist style plants, those at Lean companies reported their work load was heavier and faster. They rcported work loads were increasing and becoming faster. They reported it was difficult to change things they did not like about their job and that it was becoming more difficult to get time off. While our survey results suggest that working in traditional Fordist plants is far from paradise, they also suggest that working in Lean plants is worse. At a minimum, our results should be viewed as a wake-up call to those who have painted a positive picture of work under Lean Production.

Worker Commitment and Labour Management Relations Under Lean Production at Cami - Rinehart, James W.; Huxley, Christopher; Robertson, David (Relations industrielles / Industrial Relations, 1994)
CAMI, a unionized Suzuki-General Motors auto plant in Ontario, attempted to construct a workplace characterized by worker commitment and cooperative labor-management relations. These efforts failed. There was a 5-week strike in the Fall of 1992 at the plant. While CAMI was in the start-up mode, labor-management relations were relatively harmonious and the working environment relaxed. With the onset of full production all this changed, and the meaning of "lean" production became clearer. Workers regularly contested the dictates of lean production at CAMI. Interest and participation in quality circle and suggestion programs declined. Proponents of lean production are likely to define CAMI as an aberration by involving the partial implementation thesis or stressing the militancy of the union. In one respect only are they right. The strike does distinguish CAMI as exceptional, at least until there are similar manifestations of industrial conflict in other transplants. However, the conditions that produced the strike appear in unionized as well as non-unionized transplants.
Keywords: AUTOMOBILE industry; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Commitments; Japanese management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strikes; Studies

Union Resistance and Union Renewal in the CAW - Murningham, Bill; Robertson, David (Paths to Union Renewal: Canadian Experiences, 2006)
[D]iscusses the determinants of a strong union movement, the evolution of the union [from 1985 to 2005], and the challenges of union resistance and union renewal. These include making gains in bargaining, expanding democracy, organizing, deepening membership involvement and participation, generational renewal, strengthening social unionism, building alliances with social movements, strengthening our capacity to mobilize, and defining ourselves by what we do. The paper asserts that one of the union's greatest strengths is its culture. -- Editors' introduction
Keywords: Canadian Auto Workers (CAW); Labor Unions; Labor movement; Organizational change